Annexin A1 and A2 in inflammatory bowel disease pathogenesis: exploring new avenues for diagnosis and treatment - Murshed, Najib Muaamer Faed; Shetty, Praveenkumar; Jayaswamy, Pavan K.; Jacob, Ankeeta Menona; Alawadhi, Samah Saleh Ahmed; Hosapatna Laxminarayana, Kishan Prasad (Frontiers in Immunology, 2026)
Inflammatory bowel disease (IBD), which includes Crohn's disease and ulcerative colitis, is a significant global health burden with gastrointestinal inflammation resulting from dysfunctional immune responses and chronic inflammation. This review synthesizes the roles of annexin A1 (AnxA1) and annexin A2 (AnxA2) in the pathophysiology of IBD, their diagnostic biomarkers, and therapeutic potential. AnxA1 interacts with FPR2/ALX receptors, inhibiting the release of pro-inflammatory cytokines and promoting epithelial cell repair. AnxA2 exhibits dual roles by interacting with S100A10. AnxA2 can induce NF-κB activation, promoting pro-inflammatory cytokine release and plasminogen activation. On the other hand, AnxA2 activates the TRAM-TRIF pathway, inhibiting NF-κB activation, promoting production of anti-inflammatory cytokines, fibrinolysis, and restoring tight junctions. Their modulation of NF-κB pathways shapes the molecular landscape of IBD. AnxA1 and AnxA2 are non-invasive plasma biomarkers that improve subtype-specific diagnostic accuracy compared to C-reactive protein. In the therapeutic context, AnxA1 mimetics and AnxA2 inhibitors reduce inflammation and promote healing, potentially in conjunction with anti-TNF drugs or nanoparticle delivery. Longitudinal studies and clinical trials are essential to identify the gaps in the standardization of testing and cytokine network interactions. AnxA1 and AnxA2 have the potential to transform the development of precise diagnostics and personalized therapies, redefining the management of IBD.